2014
DOI: 10.1111/cei.12378
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes from Sjögren's syndrome patients display increased vasoactive intestinal peptide receptor 2 expression and impaired apoptotic cell phagocytosis

Abstract: SummarySjögren's syndrome (SS) is a chronic autoimmune disease characterized by salivary and lacrimal gland dysfunction. Clinical observations and results from animal models of SS support the role of aberrant epithelial cell apoptosis and immune homeostasis loss in the glands as triggering factors for the autoimmune response. Vasoactive intestinal peptide (VIP) promotes potent anti-inflammatory effects in several inflammatory and autoimmune disease models, including the non-obese diabetic (NOD) mouse model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 49 publications
(67 reference statements)
4
38
0
Order By: Relevance
“…This altered expression correlates with an impaired phagocytosis of apoptotic epithelial cells, with reduced engulfment capacity and failure to express an immunosuppressant cytokine profile that is not restored by VIP. This differential expression of VPAC2 associated with phagocytic dysfunction suggests its potential as a functional biomarker in SS [303].…”
Section: Other Autoimmune Disordersmentioning
confidence: 86%
“…This altered expression correlates with an impaired phagocytosis of apoptotic epithelial cells, with reduced engulfment capacity and failure to express an immunosuppressant cytokine profile that is not restored by VIP. This differential expression of VPAC2 associated with phagocytic dysfunction suggests its potential as a functional biomarker in SS [303].…”
Section: Other Autoimmune Disordersmentioning
confidence: 86%
“…Also, a polymorphism in the 3 0 UTR region of the VPAC1 gene was identified in RA (Delgado et al 2008a, Paladini et al 2008. In Sjogren syndrome patients, monocytes exhibit increased VPAC2 expression and are deficient in phagocytosis of apoptotic cells (Hauk et al 2014). In contrast, reduced VPAC2 expression and a distinct DNA footprinting pattern in the VPAC2 promoter were observed in Th1 cells of MS patients (Sun et al 2006).…”
Section: Vip Receptors In Immune Cellsmentioning
confidence: 99%
“…It has anti-inflammatory effects, as it inhibits proinflammatory cytokines, such as tumor necrosis factor (TNF)-α and IL-6, 33 – 35 and upregulates the anti-inflammatory cytokine IL-10. 34 – 36 However, a recent study 37 has shown that exogenous VIP did not change TNF and IL-10 levels expressed by cultured MNCs that had phagocytosed apoptotic salivary gland cells obtained from pSS patients. This study did not evaluate cytokine changes in MNCs from pSS patients under other conditions.…”
Section: Other Autoantigens In Sjögren’s Syndromementioning
confidence: 99%
“… 22 The expression of VIPR2 was recently found to be increased in monocytes from pSS patients, but unfortunately, VIPR levels were not assessed in lacrimal and meibomian glandular tissues. 37 …”
Section: Other Autoantigens In Sjögren’s Syndromementioning
confidence: 99%
See 1 more Smart Citation